Consumers Purchase Intention towards Solar Panel as Renewable Energy Source in Malaysia - Yew, Lim Kim; Kowang, Tan Owee; Yang, MengXi; Jong, Loh Chee (International Journal of Membrane Science and Technology, 2023)
Numerous studies have been undertaken, both globally and locally, to investigate influencing factors and consumer buying behaviour relationships. However, research on consumer purchase intention towards solar panel as renewable energy product in Malaysia is still lacking, and this research aims to fill the research gap. The objectives of this study to examine the factors influencing comprising of product price, product quality and advertising towards consumers’ purchase intention of solar panel in Malaysia. The data for this study were collected from 348 respondents via an online questionnaire, and hypotheses analysis was conducted using multiple regression analysis to investigate the influencing factors and consumers’ purchase intention for solar panel as renewable energy product in Malaysia. Results shown that product price, product quality and advertising have significant influence on consumers’ purchase intention towards solar panel in Malaysia as important source for energy conservation and generation.